“Hva hører du på?” - Refleksioner over ”SKAM-musikken” - Ligaard, Eva Elise (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2017)
In this article I wish to highlight some of the many ways that music functions in SKAM. In particular I wish to ask: Which role does music play in portraying the characters? How are the connotations and associations of specific songs actively used in the TV show? To answer these questions, I will unpack the cultural and historical context of certain songs and musicians and mirror this to selected scenes. I argue that SKAM, through the music selection, actively confronts the audience’s expectations to the characters and both confirms and challenges specific cultural narratives. Hereby cultural codes are turned upside down, and new interpretations are made possible. The soundtrack of SKAM is not used to stress a singular reading of the scenes, but opens up for multiple interpretations. To fans of SKAM, the pre-existing music tracks will be connected to specific scenes, and new connotations of the music appear.